Library apps to improve the digitization of Sekolah Penggerak Program - Putu Satya Saputra; Luh Putu Ary Sri Tjahyanti; Putu Aditya Pratama; Gede Rai Sutama (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2023)
Education is a planned means for human development and progress, especially in Indonesia. Education programs in Indonesia have changed from year to year. The first programs were the Rencana Pelajaran Curriculum in 1947, Pendidikan Curriculum in 1975, the Competency-Based Curriculum in 2004, the 2013 Curriculum, and the Merdeka Curriculum 2022 until now. Sekolah Penggerak Program is one of the curriculum implementations that play a role in making operations that suit the learning needs of students at school. One of the interventions in Sekolah Penggerak Program is digitizing schools using various platforms to support student learning and creativity. There are still many Sekolah Penggerak that have not maximized the use of digitalization, one of which is Pelita Kasih Kindergarten. Pelita Kasih Kindergarten is one of the Sekolah Penggerak in Buleleng Regency. Pelita Kasih Kindergarten still uses manual recording to record borrowing books borrowed by students or parents of students. These problems can hamper the learning process and are considered less efficient. Therefore, a system was developed to assist library management and book lending to minimize errors and human errors that could occur. Library system development in this study using the prototype method. The prototype method is used to allow interaction between system developers and system users, it can overcome discrepancies that may occur between developers and users. The results of information system testing using the black box method show that 91% of the functionality is appropriate and it is an indicator of the success of the designed information system.